Emily Brontë’s Musical Appropriations : From Literary Inspiration to Performative Adaptation - Guimarães, Paula (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
In comparison with the visual arts, the Brontës’ interactions with and depictions of music have received little critical attention. Besides their well-known skills in drawing and painting, all the Brontë children were competent and knowledgeable musicians; music played an important part both in their family life and in the Victorian public culture. Emily Brontë, in particular, not only possessed a collection of annotated sheet music but was also a virtuoso pianist, exhibiting a taste in both baroque and romantic styles of composition and a fondness for orchestral works. Her preferred composers included Handel, Mozart, Bach, Gluck, Schubert, Rossini, Mendelssohn and Beethoven. Critics such as Robert Wallace (1986) and Meg Williams (2008) have referred to Brontë’s ‘musical matrix’, not only her music-making but also the influence of musical ideas on her writing. The sounds of music release her imagination and she sees a transformative power in them; the music of the wind in her poems runs like a piece of organ-music between the registers of air and earth. Similarly, Wuthering Heights’s mesh of repetitions and variations and its overall rhythmic patterning recalls a ‘cosmic polyphony’. It is therefore no surprise that Emily Brontë’s work has been a source of inspiration for many musicians. As both Patsy Stoneman (1996) and Linda Lister (2008) have documented, Brontë’s only novel has inspired two major operatic realizations, several musical-theatre adaptations, and numerous songs settings by composers in the realms of both classical and popular music. The art song or aria strives to portray a particular emotional moment and Brontë’s intensely focused poetic expression suits it perfectly. On a grander scale, the high dramatic and emotional sense of Wuthering Heights and the utterances of its fiercely Romantic characters make the novel suitable for an operatic libretto.